Origin of High-Resolution IETS-STM Images of Organic Molecules with Functionalized Tips - Hapala, Prokop; Temirov, Ruslan; Tautz, F Stefan; Jelínek, Pavel (Physical review letters, 2014)
Recently, the family of high-resolution scanning probe imaging techniques using decorated tips has been complemented by a method based on inelastic electron tunneling spectroscopy (IETS). The new technique resolves the inner structure of organic molecules by mapping the vibrational energy of a single carbon monoxide (CO) molecule positioned at the apex of a scanning tunneling microscope (STM) tip. Here, we explain high-resolution IETS imaging by extending a model developed earlier for STM and atomic force microscopy (AFM) imaging with decorated tips. In particular, we show that the tip decorated with CO acts as a nanoscale sensor that changes the energy of its frustrated translation mode in response to changes of the local curvature of the surface potential. In addition, we show that high resolution AFM, STM, and IETS-STM images can deliver information about the charge distribution within molecules deposited on a surface. To demonstrate this, we extend our mechanical model by taking into account electrostatic forces acting on the decorated tip in the surface Hartree potential.